До питання про галицькі церковно-співочі традиції - Зваричук, Ж. (Студії мистецтвознавчі, 2007)
This article systematizes the sources which will give a possibility to understand the ancient Galicia church singing traditions (samolivky). The most important approach done by Ukrainian folklorists over times was the study of this topic through the research of the regional performing particularities.